Seasonal variation in muscle sympathetic nerve activity - Cui, Jian; Muller, Matthew D.; Blaha, Cheryl; Kunselman, Allen R.; Sinoway, Lawrence I. (Physiological reports, 2015)
Epidemiologic data suggest there are seasonal variations in the incidence of severe cardiac events with peak levels being evident in the winter. Whether autonomic indices including muscle sympathetic nerve activity (MSNA) vary with season remains unclear. In this report, we tested the hypothesis that resting MSNA varies with the seasons of the year with peak levels evident in the winter. We analyzed the supine resting MSNA in 60 healthy subjects. Each subject was studied during two, three, or four seasons (total 237 visits). MSNA burst rate in the winter (21.0 ± 6.8 burst/min, mean ± SD) was significantly greater than in the summer (13.5 ± 5.8 burst/min, P < 0.001), the spring (17.1 ± 9.0 burst/min, P = 0.03), and the fall (17.9 ± 7.7 burst/min, P = 0.002). There was no significant difference in MSNA for other seasonal comparisons. The results suggest that resting sympathetic nerve activity varies along the seasons, with peak levels evident in the winter. We speculate that the seasonal changes in sympathetic activity may be a contribution to the previously observed seasonal variations in cardiovascular morbidity and mortality. Our data suggest that resting sympathetic nerve activity varies along the seasons, with peak levels evident in the winter. We speculate that the seasonal changes in sympathetic activity may be a contribution to the previously observed seasonal variations in cardiovascular morbidity and mortality.